A DNA-Free Editing Platform for Genetic Screens in Soybean via CRISPR/Cas9 Ribonucleoprotein Delivery - Subburaj, Saminathan; Zanatta, Caroline Bedin; Nunn, Jennifer A. L.; Hoepers, Aline Martins; Nodari, Rubens Onofre; Agapito-Tenfen, Sarah Zanon (Frontiers in Plant Science, 2022)
CRISPR/Cas9-based ribonucleoproteins (RNP)-mediated system has the property of minimizing the effects related to the unwanted introduction of vector DNA and random integration of recombinant DNA. Here, we describe a platform based on the direct delivery of Cas9 RNPs to soybean protoplasts for genetic screens in knockout gene-edited soybean lines without the transfection of DNA vectors. The platform is based on the isolation of soybean protoplasts and delivery of Cas RNP complex. To empirically test our platform, we have chosen a model gene from the soybean genetic toolbox. We have used five different guide RNAs (gRNAs) sequences which targeted the Constitutive Pathogene Response 5 (CPR5) gene associated with the growth of trichomes in soybean. In addition, efficient protoplast transformation, concentration and ratio of Cas9 and gRNAs were optimized for soybean for the first time. Targeted mutagenesis insertion and deletion frequency and sequences were analyzed using both Sanger and targeted deep sequencing strategies. We were able to identify different mutation patterns within InDels between +5 nt up to –30 bp and mutation frequency ranging from 4.2 to 18.1 %. in the GmCPR5 locus. Our results showed that DNA-free delivery of Cas9 complexes to protoplasts is a useful approach to perform early-stage genetic screens and anticipated analysis of Cas9 activity in soybeans.